Viability of Joint Forest Management Projects - Chaturvedi, A. N. (Indian Forester, 2000)
This paper contends that Joint Forest Management projects have been initiated by government and are not a spontaneous response of people to safeguard forests. The NGOs involvement is only to serve their own vested interests. Pressure oflivestock grazing is at least eight times more than what the forest areas can support. Lopping of tree leaves for fodder and sweeping of forest floors has drastically reduced the growth of forests. Kautilya’s Arthasastra clearly mentions that in times of the Maurya kings the forests and pasture lands belonged to the State. Dispassionate and unbiased analysis of present day facts show that Joint Forest Management projects are not sustainable in the long run.